Trade-offs between bird diversity and abundance, yields and revenue in smallholder oil palm plantations in Sumatra, Indonesia. (June 2015) - Teuscher, Miriam; Vorlaufer, Miriam; Wollni, Meike; Brose, Ulrich; Mulyani, Yeni; Clough, Yann
Abstract: Global land-use change has drastic consequences for biodiversity leading to losses of ecological functioning, ecosystem services and human well-being. While species dependent on undisturbed natural habitat are most affected by conversion to agriculture, even populations of disturbance-tolerant species can be endangered in landscapes dominated by high-input mono-cultural cropping systems. This has raised the question of how, and at what cost, a diversity of species can be conserved in such habitats. Focusing on birds of smallholder oil palm-dominated landscapes, we investigated the relationship between the ecological and economic outcomes of remnant or planted trees in smallholder oil palm plantations. The study comprised a household and a field component. We gathered plot specific data on yields, revenue and inputs from 120 households owning productive oil palm plantations in the Jambi Province, Sumatra, Indonesia. Bird diversity and abundance as well as vegetation structure was assessed on the same oil palm plots. We tested the effects of a set of economic and ecological variables on measures of bird diversity, bird abundance, oil palm yield, and total revenue. Our results show that a gain in bird diversity and bird abundance conditional on increases in number of trees comes along with a loss in revenue for farmers indicating that there is a win–lose relationship between ecological and economic functions. However, since the relationship is non-linear, costs for bird species gain or gain in bird abundance change depending on the number of trees within an oil palm plantation: in a relatively extensively managed oil palm plantation (high number of trees, low oil palm yields), a further increase in the number of bird species or individuals leads to a relatively high loss in total revenue, whereas in an intensively managed oil palm plantation the same increase in number of bird species results in a smaller loss in revenue. An increase in bird abundance can be fostered at smaller costs when compared to the costs for increasing biodiversity. This suggests that there is room for tree-based enrichment of intensively managed oil palm plantations, where a relatively high increase in bird species richness or bird abundance could be achieved at relatively low cost.